PENGARUH METODE PENGAJARAN BERBASIS TAKSONOMI BLOOM PADA PEMBELAJARAN SPEAKING BAHASA INGGRIS ANAK ANAK DI PERUMNAS ROYAL RESIDENCE 02 RT 29 - Azzahra, Novrida; Novela, Lisa; Khoirun Nisa, Dila; Meilena Sari, Widea; Al Mubarak, Abdussalam; Revola, Yashori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to speak English is a skill that should be honed starting in elementary school. It is vital for developing communication skills, self-confidence, and students’ readiness to navigate educational advancements in an increasingly globalized world. However, the process of learning to speak English among children is often hindered by various factors, such as limited opportunities for speaking practice, a lack of self-confidence, and a curriculum that focuses more on theory than on practice. This community service activity aims to demonstrate the application of speaking instruction developed based on Bloom’s Taxonomy, with the goal of improving children’s English speaking skills through the English Language Teaching for Young Learners program. This program was implemented at Al-Hidayah Mosque, Royal Residence 02 Housing Complex, RT 29, Bumi Ayu Village, Bengkulu City, using a Community Asset-Based Empowerment (ABCD) approach that optimizes the community’s potential to support the learning process. The method used is Interactive Learning based on Microteaching, which integrates the six levels of Bloom’s Taxonomy: recall, understand, apply, analyze, evaluate, and create. The learning materials cover greetings, self-introductions, expressing thanks and apologies, and saying goodbye through conversation practice, role-playing, storytelling, games, and other communication activities. The results of this study indicate that Bloom’s Taxonomy approach can enhance students’ active participation, confidence, and ability to use simple English sentences in the context of everyday communication. In addition, interactive and step-by-step learning creates an enjoyable learning environment, making students more confident in communicating in English. Thus, speaking instruction that combines Bloom’s Taxonomy with the ABCD approach has proven to be an effective learning model for improving English communication skills among elementary school-aged children in community service activities.